India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
Despite the external origin of the financial crisis, the potential impact on India's corporate sector could be large, as India has become increasingly integrated with the global economy in the past decade. The Selected Issues paper discusses India's economic development and policies. The impact on the corporate sector will in turn feed into India's overall economic growth. The significant volatility in the exchange equity prices, and interest rates triggered by the global crisis, together with the decline in global economic activity and capital flows, will weight on India's firms.